Análise do comportamento mecânico de concreto reforçado com fibras de aço recicladas - Coelho, Luiza Campos (2023)
Aiming to minimize environmental impacts, several scientists are looking at ways to recycle, reuse and take advantage of materials that have reached the end of their useful life, such as waste tires, which generate millions of tons of discarded materials per year. Following resolutions from environmental agencies, the tire industry began to divert waste tires so that the components could be used as inputs in other industries. Recent studies point to a potential replacement of industrial steel fibers, used as reinforcement in concrete structures in civil construction, with steel fibers extracted from scrap tires. Therefore, this exploratory research carried out a Systematic Literature Review – RSL on the topic and an experimental program. RSL presented an overview of research on the subject and guided the development of the experimental program based on a broad analysis of the experimental studies analyzed. The experimental program separated and characterized the FAR used in the research, also characterized the constituent materials of the CRF, and characterized the CRF in the fresh state and in the hardened state, varying the type of fiber added in FAR and FAI; and the addition content, in: 0, 0.3% and 0.6%. To understand the influence of adding fibers in the fresh state, the slump and frustum tests and the entrained air test were carried out. To analyze the behavior in the hardened state, tensile, compression and flexion tests were carried out. From the RSL it was possible to conclude that industrial steel fibers can be replaced by recycled steel fibers without significant losses in the mechanical properties of the structural element, under the actions of compression, tension, shear and flexion. Likewise, from the experimental program, it was possible to conclude that FAR added to concrete decreases the workability of the mixture, increases the porosity of the mixture, decreases the compressive strength, increases the tensile strength, increases the flexural strength, provide a decrease in residual resistance; In general, the behavior was similar to the behavior of the FAI. It is important to highlight that the comparison between fiber types is complex due to the heterogeneity of FAR characteristics.